Price Changes and the Rate of Change of Money Wage Earnings in the Light of American Data - Holt, Charles C.; Lee, Kyu Sik (Quarterly Journal of Economics, 1967)
Journal Article Price Changes and the Rate of Change of Money Wage Earnings in the Light of American Data Get access Charles C. Holt, Charles C. Holt University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar Kyu Sik Lee Kyu Sik Lee University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 2, May 1967, Pages 347–350, https://doi.org/10.2307/1879594 Published: 01 May 1967